Radiofrequency Ablation of Hepatocellular Carcinoma (≤ 5 cm) with Saline-Perfused Electrodes: Factors Affecting Local Tumor Progression - Kim, Dong Ho; Chung, Dong Jin; Cho, Se Hyun; Han, Joon-Yeol (Journal of the Korean Society of Radiology, 2020)
Purpose We aimed to assess local tumor progression (LTP) rate and associated prognostic factors in 92 patients who underwent radiofrequency ablation (RFA) using saline-perfused electrodes to treat hepatocellular carcinoma (HCC) (≤ 5 cm). Materials and Methods Total 92 patients with 148 HCCs were treated with RFA using salineperfused electrodes, from 2009 to 2015. We retrospectively evaluated technical success, technique efficacy, and LTP rates. Potential prognostic factors for LTP were perivascular tumor, subphrenic tumor, artificial ascites, tumor size (≥ 2 cm), and previous treatment of transarterial chemoembolization. Analysis was performed by lesion, rather than by person. Results During follow-up period from 1 to 97.4 months, total cumulative LTP rates were 7.9%, 11.4%, and 14.6% at 1, 3, and 5 years, respectively. These values were significantly higher in the perivascular (35.1%; p = 0.009) and subphrenic group (38.9%; p = 0.002) at 5-year. We did not observe any significant difference in LTP according to other prognostic factors (p > 0.05). Conclusion RFA with saline-perfused electrode is a safe and effective treatment modality for HCC (≤ 5 cm), with lower LTP rates. Nevertheless, perivascular and subphrenic HCCs demonstrated higher LTP rate than other sites. It is imperative to note that perivascular and subphrenic location of HCC are associated with a high risk of local recurrence, despite the use of salineperfused electrodes.